Diagnostics Of The Metal Cutting Process Based On Electrical Signals - Mamurov, Eldor Tursunovich (Central Asian Journal of Theoretical and Applied Science, 2022)
The article deals with the use of electrical phenomena occurring in the process of cutting metals as an informative parameter for diagnosing the performance of a cutting tool and controlling cutting conditions.